Travelers to the FIFA world cup 2014 in Brazil: Health risks related to mass gatherings/sports events and implications for the Summer Olympic Games in Rio de Janeiro in 2016 - Eberhardt, K. A.; Vinnemeier, C. D.; Dehnerdt, J.; Rolling, T.; Steffen, R.; Cramer, J. P. (Travel Medicine and Infectious Disease, 2016)
Background: Health threats during mass gatherings, such as the FIFA world cup 2014 differ from traditional health risks. The influence of event type, demographics of attendees and environmental conditions are still not fully understood.